Perancangan Aplikasi Antrian Kunjungan Pasien Rawat Jalan Berbasis Web Di Uptd Puskesmas Pakan Rabaa Tahun 2024 - Yulfa, Yulfa_Yulia2025; Rahma Qori’ah; Yanti Desnita Tasri (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2025)
Incompleteness in filling out medical record files causes records to become out of sync and patient health information is difficult to identify. The initial medical assessment form is considered complete if the identification, authentication, and recording items are met. Based on the initial survey, it was found that 8 out of 10 initial medical assessment forms were incomplete at Reksodiwiryo Hospital in Padang. This study aims to review the completeness of completing the initial medical assessment for internal medicine patients at RST Reksodiwiryo on 1-3 July 2024. This research is a quantitative study with a descriptive approach, with a population of 3,818 initial assessment forms and a sample of 97 forms. Data was collected using observation with a checklist table instrument and analyzed using editing, coding, processing and cleaning techniques with univariate analysis. The results showed that of the 97 initial medical assessment forms for outpatient internal medicine patients, 14 (14.4%) were incomplete in identification, 50 (51.5%) were incomplete in recording, and 77 (79.4%) were incomplete in authentication. In total, 62 (63.9%) forms were incomplete. In conclusion, more than half of the initial medical assessment forms for internal medicine patients at TK.III Dr. Hospital. Reksodiwiryo Padang is incomplete. It is recommended that medical personnel fill out the initial medical assessment form for outpatients completely and thoroughly in accordance with the hospital's SOP. ​Keywords:[Applications, Queues, Unified Modeling Language (UML), websites]